New regimen for eccentric calf-muscle training in patients with chronic insertional Achilles tendinopathy: results of a pilot study. Issue 9 (9th January 2008) - Jonsson, P; Alfredson, H; Sunding, K; Fahlström, M; Cook, J
Abstract : Background: Chronic painful insertional Achilles tendinopathy is seen in both physically active and non-active individuals. Painful eccentric training, where the patients load the Achilles tendon into full dorsiflexion, has shown good results in patients with mid-portion Achilles tendinosis. However, only 32% of patients with insertional Achilles tendinopathy had good clinical results with that type of eccentric training regimen. Aim: To investigate whether a new model of painful eccentric training had an effect on chronic painful insertional Achilles tendinopathy. Patients and methods: 27 patients (12 men, 15 women, mean age 53 years) with a total of 34 painful Achilles tendons with a long duration of pain (mean 26 months), diagnosed as insertional Achilles tendinopathy, were included. The patients performed a new model of painful eccentric training regimen without loading into dorsiflexion. This was done as 3×15 reps, twice a day, 7 days/week, for 12 weeks. Pain during Achilles-tendon-loading activity (VAS) and patient's satisfaction (back to previous activity) were evaluated. Results: At follow-up (mean 4 months) 18 patients (67%, 23/34 tendons) were satisfied and back to their previous tendon-loading activity. Their mean VAS had decreased from 69.9 (SD 18.9) to 21 (SD 20.6) (p<0.001). Nine patients (11 tendons) were not satisfied with the treatment, although their VAS was significantly reduced from 77.5 (8.6) to 58.1 (14.8) (p<0.01). Conclusion: In this short-term pilot study this new model of painful eccentric calf-muscle training showed promising clinical results in 67% of the patients.